IMPLEMENTASI VISI PROFETIK: BERMAKRIFAT MELALUI HUTAN - Nasruddin Anshoriy (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article discusses about a teaching to respect all God’s creatingto build a harmonious relation. Understanding the human beings leadsthe people to understand God’s character. The object of the research isthe forest and it is analyzed philosophically by revealing the meaninginside. It is found that there is a dialectic among the forest, human, andGod which is essential for man’s life. Beside that, by protecting the forestthe people as a leader (khalifah) can be closer to God.